Academic related anxieties: A case study investigating the relationships among library, communication and language anxieties among non-native speakers of English - Sinnasamy, Janaki; Abdul Karim, Noor Harun; Sinnasamy, Janaki; Abdul Karim, Noor Harun (Malaysian Journal of Library and Information Science, 2017)
Sinnasamy, J., & Abdul Karim, N. H. (2015). Academic related anxieties: A case study investigating the relationships among library, communication and language anxieties among non-native speakers of English. Malaysian Journal of Library & Information Science, Vol.20, no. 2: 1-12 Library anxiety has been identified as one of the academic related anxieties which can affect college students. The Library-Anxiety-Expectation Model indicated innate characteristics of students and environmental variables such as gender, race, and year of study, as possible antecedents of library anxiety. This means that the arousal of library anxiety can be influenced by students' other forms of inherent anxieties. The objective of this paper is therefore to investigate the level of academic related anxieties among final year undergraduates and the relationships among the dimensions of the anxieties. The scope of this study focuses on three anxieties; library anxiety, English language anxiety and communication anxiety. Three sets of survey instruments were used; Library Anxiety Scale (LAS), Foreign Language Classroom Anxiety Scale (FLCAS), and Personal Report of Communication Apprehension (PRCA-24). All instruments were translated into the Malay language and statements with the word ‘foreign language’ in FLCAS were changed to ‘English language’. The findings showed that final year students in this study experience only a moderate level of all three academic related anxieties. It was found that all four dimensions of communication anxiety – formal, interpersonal conversations, group discussion, and public speaking – correlated with at least one or more of the five dimensions of library anxiety – barriers with staff, library services barriers, library resources barriers, affective barriers, and internet services barriers. All three dimensions of language anxiety – speaking anxiety, classroom anxiety, and learner anxiety – correlated with at least one or more of library anxiety dimensions. Although the correlations were moderate, the study nevertheless provided empirical evidence that the dimensions of communication and language anxieties have relationship with the dimensions of library anxiety. Acknowledgment of the prevalence of these anxieties among students can help libraries and librarians to make learning in the library less stressful by focusing more on students and their problems instead of the library and its environment only.